Adapting Traceability in Digital Forensic Investigation Process - Selamat, S. R.; Yusof, R.; Sahib, S.; Roslan, I.; Abdollah, M. F.; Mas'ud, M. Z. (2011)
Generally, the goals of digital forensic investigation process in a cyber crime are to identify the origin of the incident reported as well as maintaining the chain of custody so that the legal process can take its option. However, the traceability process has become a key or an important element of the digital investigation process, as it is capable to map the events of an incident from different sources in obtaining evidence of an incident to be used for other auxiliary investigation aspects. Hence, this paper introduces the adaptability of the traceability model to illustrate the relationship in the digital forensic investigation process by integrating the traceability features. The objective of this integration is to provide the capability of trace and map the evidence to the sources and shows the link between the evidence, the entities and the sources involved in the process. Additionally, the proposed model is expected to help the forensic investigator in obtaining accurate and complete evidence that can be further used in a court of law.